Research on the Low-Carbon Development Path and Policy Options of China’s Transportation Under the Background of Dual Carbon Goals - Wang, Xuecheng; Zhou, Yalin; Bi, Qinghua; Cao, Zilong; Wang, Baochun (Frontiers in Environmental Science, 2022)
Chinese government has proposed ambitious targets to combat climate change. As carbon emissions of China’s transportation have been increasing rapidly in past decades, massive efforts for carbon reduction need to be taken by transportation sector. Research is needed to provide practical action paths for low-carbon development in the transport sector. Based on the historical carbon emissions in the transportation sector and the new possible trends in the future, this paper uses a forecast model to predict China's transportation energy consumption and emission demand. Then we adopt a scenario analysis to analyze the total transportation demand in the transportation sector from 2021 to 2060. We quantitatively simulate the emission reduction effects of different policy measures under different scenarios, such as optimization of transportation structure, application of energy-saving and emission-reduction technologies, and new energy applications. The research results provide decision support for China's green transportation planning goals and management policy formulation.